DEVELOPMENT OF â€œISAYHEARTâ€ MOBILE APPLICATION TO MONITOR HEALTH DATA AMONG GENERAL POPULATION IN MALAYSIA - Abdul Hapes Mohammed; Muhammad Hakimi Ahmad; Norfiza Ibrahim; Nadia Abdul Wahab (Journal of Islamic, Social, Economics and Development, 2022)
The development of mobile health applications has gotten a lot of attention recently, with some researchers referring to it as the future of healthy living. These mobile health apps serve as an alternative to traditional health monitors. Because most smartphones at present come with advanced sensors and technology, they can be utilized for a variety of purposes and services. These apps could be used almost anywhere and at any time. Nonetheless, many people are unaware of this advancement due to a lack of knowledge and exposure of mhealth. The goal of this study is to create a mobile health software that can be utilized by Malaysian, regardless of their age and location. Without the presence of a doctor or medical aid, the mobile application allows users to track and monitor their health. Therefore, it is essential to make use of this new rising technology to create a mobile health application that promotes mHealth in Malaysia. Planning, requirement analysis, design, development, testing and maintenance, and documentation are the six phases of the Agile Methodology that is used to guide this study. The Google Android Studio is used in the design and development of the mobile application. Among the features of this mobile application are a body mass index (BMI) calculator, vital scans, nearest hospitals, and articles search. The evaluation of the mobile application is done by using User Acceptance Test. The results reveal that most of the participants feels that this application has a good usability and they feel satisfied with this application as technology is so readily available, creating a mobile health application system can benefit the community by giving a cost-effective tool for monitoring and tracking their health.